Design and implementation of embedded multi-sensor outdoor robot localization system using FPGA / Hayder Ali Hussein. - Hussein, Hayder Ali (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The research objectives are to design and implement of embedded multi sensor outdoor robot for localization system using FPGA DE0-Nano board ; to implement an obstacles avoidance system by using multi-sensors ; to implement the path planning algorithm for autonomous robot.